An Indo-Pacific coral spawning database - Zarinah Waheed (Nature Publishing Group, 2021)
The discovery of multi-specific synchronous spawning of scleractinian corals on the Great Barrier Reef in the 1980s stimulated an extraordinary effort to document spawning times in other parts of the globe. Unfortunately, the majority of these data remain unpublished, partly due the reluctance of many journals to publish descriptive data. Consequently, many aspects of coral reproductive phenology remain poorly understood. The Coral Spawning Database (CSD) collates much of these disparate data into a single place. The CSD includes 5791 observations of the time or day of spawning for 329 species in 61 genera from 168 sites in the Indo-Pacific. The goal of the CSD is to provide open access to coral spawning data to accelerate our understanding of coral reproductive biology.